Percepção de consumidores diante da rotulagem nutricional frontal de alimentos embalados - Lima, Danielle Esthefane Sousa (2023)
The high consumption of added sugars, saturated fats and sodium is a public health problem, as a result, measures have been adopted to reduce damage to the health of the population. Frontal Nutritional Labeling (FRN) can be an efficient tool capable of providing better choices among consumers. Recently, the National Health Surveillance Agency (ANVISA) made it mandatory to apply the magnifying glass RNF in Brazil, for packaged foods in the absence of the consumer. In view of this, we investigated the perception of consumers regarding RNF in packaging of real products sold in Brazil with high levels of saturated fat and/or sodium, which affect perceptions, emotions, purchase intention and consumer choices of these products. The study was conducted through online questionnaires, where the packaging of products sold in Brazil with high levels of saturated fat and/or sodium were presented with or without RNF. Consumers evaluated and reported their purchase intention, perceptions, feelings, emotions and choices regarding packaging. It was possible to observe significant differences in consumers' perceptions of food packages with traffic light RNF and magnifying glass. The magnifying glass RNF was the one that most negatively affected intentions and perceptions regarding choices. The magnifying glass was also the most efficient in indicating the least healthy product to the consumer and its use allowed consumers to make healthier choices. These results show that the use of the magnifying glass RNF can lead to loss of sales by industries that sell products with high levels of saturated fat and sodium. Industries will have to reformulate their products to avoid the need to apply the magnifying glass RNF on their packaging. Thus, with lower levels of saturated fat and sodium in foods, the risks of diseases such as obesity, diabetes, hypertension and cardiovascular diseases are reduced.